1990
DOI: 10.1128/jvi.64.5.1973-1983.1990
|View full text |Cite
|
Sign up to set email alerts
|

Four major sequence elements of simian virus 40 large T antigen coordinate its specific and nonspecific DNA binding

Abstract: By mutational analysis, we have identified a motif critical to the proper recognition and binding of simian virus 40 large tumor antigen (T antigen) to virus DNA sequences at the origin of DNA replication. This motif is tripartite and consists of two elements (termed A1 and B2) that are necessary for sequence-specific binding of the origin and a central element (B1) which is required for nonspecific DNA-binding activity. Certain amino acids in elements A1 (residues 152 to 155) and B2 (203 to 207) may make dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…Some viral proteins undergo nucleic acid-dependent oligomerization in a sequence-specific manner, an example of which is the Borna disease virus (BDV) nucleoprotein which requires the presence of 5′-specific BDV RNA for its oligomerization (Hock et al, 2010). Most famously, the main regulatory protein of all polyomaviruses, LT-Ag, binds to the origin of the viral DNA replication sequences in a double hexameric forms to initiate viral DNA replication (Auborn, Markowitz, Wang, Yu, & Prives, 1988;Lynch & Frisque, 1990;Simmons, Loeber, & Tegtmeyer, 1990;Simmons, et al 2004). , 2006).…”
Section: Stable Dimer and Oligomer Formation By Polyomavirus Agnoprmentioning
confidence: 99%
“…Some viral proteins undergo nucleic acid-dependent oligomerization in a sequence-specific manner, an example of which is the Borna disease virus (BDV) nucleoprotein which requires the presence of 5′-specific BDV RNA for its oligomerization (Hock et al, 2010). Most famously, the main regulatory protein of all polyomaviruses, LT-Ag, binds to the origin of the viral DNA replication sequences in a double hexameric forms to initiate viral DNA replication (Auborn, Markowitz, Wang, Yu, & Prives, 1988;Lynch & Frisque, 1990;Simmons, Loeber, & Tegtmeyer, 1990;Simmons, et al 2004). , 2006).…”
Section: Stable Dimer and Oligomer Formation By Polyomavirus Agnoprmentioning
confidence: 99%
“…We have mapped nonspecific DNA binding to a region between aa residues 131 and 517 (75). Recently, we showed that at least 5 residues (mapping between positions 149 and 203) within the DNA binding domain were important in binding nonspecifically to doubleand single-stranded DNAs (51,52). All mutations in the domain which significantly reduced nonspecific binding also prevented originspecific binding (although the converse was not true).…”
mentioning
confidence: 98%
“…These activities include pro-tein oligomerization (74), binding to single-stranded DNA (49,75), interactions with cellular factors (31), and DNA unwinding and helicase activities (74,75,92). In light of this complexity, it is not surprising that the T-ag-bd is itself organized into subdomains (73). The solution structure of the T-ag-bd region between amino acids 131 and 260 (T-ag-bd 131-260 ) has provided preliminary insights into these processes (44).…”
mentioning
confidence: 99%